2001
DOI: 10.1152/ajpregu.2001.281.6.r1887
|View full text |Cite
|
Sign up to set email alerts
|

Comparative actions of adrenomedullin and nitroprusside: interactions with ANG II and norepinephrine

Abstract: The role of adrenomedullin (ADM) in volume and pressure homeostasis remains undefined. Accordingly, we compared the biological responses to infusions of ADM and nitroprusside (NP; matched for reduction of arterial pressure) and assessed their effects on responses to ANG II and norepinephrine in eight conscious sheep. During matched falls in arterial pressure (8-10 mmHg, both P < 0.001) ADM and NP induced similar increases in heart rate. ADM increased cardiac output (P < 0.001), and the fall in calculated perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…Fewer studies have reported diuresis or natriuresis in normal animals or man at physiologically relevant doses of ADM (Charles et al 1997, Lainchbury et al 1997, Troughton et al 2000. However, we have observed that modest increments in plasma ADM are clearly diuretic and natriuretic in normal sheep relative to infusions of nitroprusside which induced matched falls in arterial pressure (and presumably renal perfusion pressure) (Charles et al 2001). Further, McGregor et al (2001 observed that ADM was diuretic and natriuretic in patients with IgA nephropathy.…”
Section: Discussionmentioning
confidence: 69%
“…Fewer studies have reported diuresis or natriuresis in normal animals or man at physiologically relevant doses of ADM (Charles et al 1997, Lainchbury et al 1997, Troughton et al 2000. However, we have observed that modest increments in plasma ADM are clearly diuretic and natriuretic in normal sheep relative to infusions of nitroprusside which induced matched falls in arterial pressure (and presumably renal perfusion pressure) (Charles et al 2001). Further, McGregor et al (2001 observed that ADM was diuretic and natriuretic in patients with IgA nephropathy.…”
Section: Discussionmentioning
confidence: 69%
“…These actions include lowering of arterial pressure associated with increases in cardiac output and falls in peripheral resistance (Charles et al 1997, Lainchbury et al 2000, Troughton et al 2000. We have previously reported the effects of AM compared with pressure-matched NP in another group of sheep undergoing similar experiments but without concurrent CSNA recordings (Charles et al 2001). Less clear is whether baroreceptor-mediated increases in sympathetic activity (for a given change in blood pressure) are altered by AM compared with NP, a standard agent used for assessing baroreflex-modulated responses to vasodilation (Casadei & Paterson 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Each animal was studied on three occasions receiving vehicle (haemaccel) control, AM and NP using a study design similar to our previous study (Charles et al 2001). AM was infused i.v.…”
Section: Methodsmentioning
confidence: 99%
“…CGRP activates CL-R-RAMP1 while AM and AM-2 activate the CL-R-RAMP2 and CL-R-RAMP3 receptor complexes. Activation of these receptor complexes by CGRP (Gnaedinger et al 1989), AM (Charles et al 2001), and AM-2 (Charles et al 2006) results in a number of hemodynamic actions including lowering blood pressure and peripheral resistance while increasing heart rate and cardiac output. These changes are also associated with significant activation of PRA.…”
Section: Discussionmentioning
confidence: 99%
“…of the study. Repeated-measures ANOVA is appropriate as it simultaneously incorporates the time and treatment (within animal) effects without direct recourse to numerous pairwise comparisons, and is thus routinely used in this context with group sizes of five to eight using similar experimental design (Charles et al 1990(Charles et al , 1991(Charles et al , 2001(Charles et al , 2006. The appropriateness of the parametric analysis has been confirmed with attention to graphical displays of the residuals from the models confirming appropriate normality.…”
Section: Bioactivity Of Ovine Crsp-1 In Conscious Sheepmentioning
confidence: 98%